The Use Of Speed Reading To Boost Reading Comprehension For First Grade Students At SMA Muhammadiyah Rappang - Nadirah Nadirah; Roni Roni; Isumarni Isumarni; Nurhikmah Nurhikmah (La Ogi : English Language Journal, 2023)
In this study, first grade students at SMA Muhammadiyah Rappang used speed reading to improve their reading comprehension. A writer and an observer participated in this research together with 40 other students in class X-1. A CAR (classroom action research) was used to carry out the study. The results suggested that improving the pupils' reading abilities might be accomplished by using speed reading techniques. The use of speed reading techniques could be successful if they were backed up by the teacher's capacity to arrange learning in the classroom by incorporating exercises proportionately in the teaching process. By providing adequate infrastructure and study facilities, a conducive learning environment was maintained. The pupils' enthusiastic responses and active engagement in each learning activity demonstrated the effectiveness of the speed reading technique.